Welcome to Westonci.ca, your one-stop destination for finding answers to all your questions. Join our expert community now! Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
Simply make the substitution.
P = 3a + 4b -6c a=2, b=3, c=-1.
P = 3*(2) + 4*(3) - 6*(-1) Multiply out.
P = 6 +12 +6 = 24.
P = 24.
Happy exams.
P = 3a + 4b -6c a=2, b=3, c=-1.
P = 3*(2) + 4*(3) - 6*(-1) Multiply out.
P = 6 +12 +6 = 24.
P = 24.
Happy exams.
Oh this is easy! Basically you use substitution - so you put in the numbers into the letters:
P = 3a + 4b -6c a = 2 b = 3 and c = -1
(PUT NUMBERS INTO LETTERS)
P = 3(2) + 4(3) - 6(-1)
P = (3x2) + (4x3) -(6x-1)
P = 6 + 12 + 6
P = 24
P = 3a + 4b -6c a = 2 b = 3 and c = -1
(PUT NUMBERS INTO LETTERS)
P = 3(2) + 4(3) - 6(-1)
P = (3x2) + (4x3) -(6x-1)
P = 6 + 12 + 6
P = 24
Thank you for choosing our service. We're dedicated to providing the best answers for all your questions. Visit us again. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Thank you for choosing Westonci.ca as your information source. We look forward to your next visit.